Priming in word stem completion tasks: comparison with previous results in word fragment completion tasks - Soler, María J.; Dasí, Carmen; Ruiz, Juan C. (Frontiers in Psychology, 2015)
This study investigates priming in an implicit word stem completion (WSC) task by analyzing the effect of linguistic stimuli characteristics on said task. A total of 305 participants performed a WSC task in two phases (study and test). The test phase included 63 unique-solution stems and 63 multiple-solution stems. Analysis revealed that priming (mean = 0.22) was stronger in the case of multiple-solution stems, indicating that they were not a homogeneous group of stimuli. Thus, further analyses were performed only for the data of the unique-solution stems. Correlations between priming and familiarity, frequency of use, and baseline completion were significant. The less familiar words, which were less frequent, had higher priming values. At the same time, the stems with lower baseline completion generated more priming. A regression analysis showed that baseline completion was the only significant predictor of priming, suggesting that the previous processing of the stimuli had a greater impact on the stimuli with low baseline performance. At the same time, baseline completion showed significant positive correlations with familiarity and frequency of use, and a negative correlation with length. When baseline completion was the dependent variable in the regression analysis, the significant variables in the regression were familiarity and length. These results were compared with those obtained in a study using word fragment completion (WFC) by Soler et al. (2009), in which the same words and procedure were employed. Analysis showed that the variables that correlated with priming were the same as in the WSC task, and that completion baseline was the variable that showed the greatest predictive power of priming. This coincidence of results obtained with WFC and WSC tasks highlights the importance of controlling the characteristics of the stimuli used when exploring the nature of priming.